Contemporary chief information officers management experiences - Hunter, M. Gordon. (Gale virtual reference library, 2007)
Explores the experiences of the contemporary Chief Information Officer in the United States, Taiwan, and New Zealand. This role is now more of the management role with focus on employing technology to address business goals. CIO must know the expectations of senior management and everyone must concur on how they will meet corporate objectives.